The factors encouraging on knowledge sharing using web 2.0 technologies among undergraduates: a special reference of business studies students at vavuniya campus - Jesuthasan, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Knowledge sharing is becoming more and more important as such educational institutions are trying to harness this opportunity to students’ learning environment in order to create value. Therefore, the motivation behind this research is to conduct an empirical study to explore the factors that influence the success of knowledge-sharing using web technologies among students in higher education. A total number of 250 respondents were used in this study after removing the outliers from the actual data collected in faculty of management & commerce Students University of Jaffna. Based on the research model, exploratory factor analysis, multiple regression analysis was conducted. The findings indicate trust, real time, self-efficacy, experience, technology availability, speed of IT, perceived usefulness of technology, and user friend-ness were the significant variables that influence knowledge sharing using web 2.0 technologies in the university. The paper provides recommendations to the organization how to foster motivating students for using web 2.0 technologies for work purposes in knowledge sharing. In the discussion, a short summary of our study, managerial implications and new research direction are presented.
Keywords: Higher Education; Knowledge Sharing; Web 2.0 technologies